Design of a Novel Ultra-Wideband Semicircular Printed Antenna with Dual-Band Notched Characteristic - Najafpur, Mahdi; Nourinia, Javad; Jazi , Fateme Azamian (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A compact semicircular printed antenna with dual-band notched characteristic is proposed. A narrow rectangular slot is etched on the radiation patch to prevail notch band at 5.13-5.87 GHz for WLAN. By using two circular slots (C-shaped) defected ground structure, another notch band, at 7.59-9.03 GHz for some C-band satellite communication systems, is achieved. Due to the shape of the proposed antenna, the total dimension of this structure occupies very small space. The antenna is successfully simulated and measured. A simple 50-? microstrip line is used to excite the slot. The parameters and dimensions of the antenna have been investigated by using HFSS. Results demonstrate that the suggested antenna with small size of 20×20×1 mm3 has desired bandwidth range from 2.6-13.3 GHz for VSWR?2, except two notch bands.